Interoperability Standards and the Potential of Interoperability. Issue 3 (May 2016) - McCartney, Patricia
Abstract : As any nurse who uses an electronic medical record knows, interoperability between systems is a huge problem. While caring for one patient, a nurse may have to interact with multiple systems, none of which "talk to each other", requiring a significant amount of duplicate documentation, extra time, risk of error, and overall unneeded frustration. Measures of progress on interoperability for nursing are discussed and a general update is provided by our HIT expert Dr. McCartney.